Introduction of Criminal Liability for Prohibited Biomedical Researches in Lithuania - Levon, Justyna; Murauskas, Donatas (Teisė, 2019)
The Criminal Code of the Republic of Lithuania establishes criminal liability for prohibited biomedical research involving human beings or human embryos. This paper examines the historical origins and development of criminal liability for biomedicial research within the Lithuanian legal framework. Consideration is given as to what legal virtues (goods) are at risk when prohibited biomedical research is conducted. In this context, the authors discuss issues related to the structure of legal rule imposing criminal liability for prohibited biomedical research in Lithuania.
Keywords: biomedical research; criminal liability; the Oviedo Convention; dignity; human rights